Demokratie ohne Grund – kein Grund für Demokratie?: Zum Verhältnis von Demokratie und Poststrukturalismus - Sievi, Luzia (transcript, 2017)
Poststructuralism deconstructs liberal-democratic concepts and rejects ultimate justifications for normative ordering. For this reason, critics accuse it of being incompatible with a democratic position. Derrida, Butler, Laclau, and Mouffe represent, however, a radical future form of democracy. How can this 'ethical turn' be evaluated? How did these scholars derive reasons for democracy from an alleged groundlessness? Luzia Sievi delivers a detailed analysis of both the critiques of democracy as well as the above-mentioned thinkers' outlines of democracy. In doing so, she shows the values and findings which caused harsh critics of democracy to become strong advocates for it.